Second harmonic response of magnetic nanoparticles under parallel static field and perpendicular oscillating field for magnetic particle imaging - Satoshi Ota; Kizuku Nishimoto; Tsutomu Yamada; Yasushi Takemura (AIP Advances, 2020)
The second harmonic signal of a magnetic nanoparticle in an oscillating magnetic field was enhanced, by applying a static bias field. To promote the second harmonic signal, the oscillating field was applied perpendicular to the signal detection and static bias field. The second harmonic signal, detected in this study, was significantly higher than that of the third harmonic signal detected without a static bias field. It was also significantly higher than that of the second harmonic signal with the static bias and oscillating drive field parallel to the signal detection direction, as in the conventional setup of previous studies. The second harmonic signal dependence on the intensity of the static bias field showed that the signal intensity had a maximal value beyond the field free point (FFP), despite the maximal third harmonic existing within the FFP. In our system, the odd numbered harmonics, including the fundamental harmonic, were no longer detected. This is because the fundamental signal had a frequency twice that of the applied oscillating field. This may contribute to a significantly higher signal to noise ratio for magnetic particle imaging (MPI). In addition, the full width at half maximum associated with MPI resolution was constant with drive field amplitude, which contributes to high signal intensity and resolution, concurrently.